2012
DOI: 10.1055/s-0032-1321847
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Febuxostat in Healthy Chinese Volunteers

Abstract: Compared with the previous study, the pharmacokinetics of febuxostat appeared to be different between Chinese and other races.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 10 publications
2
31
1
Order By: Relevance
“…At the standard daily dosage of 20 mg leflunomide, the average steady-state plasma concentration of A77 1726 is approximately 125 μM (Bohanec Grabar et al, 2009; Rozman, 2002). Pharmacokinetic studies have shown that plasma/serum concentrations of A77 1726 are dose proportional following either single (20–100 mg) or repeated doses (5–25 mg daily) of leflunomide (Li et al, 2002; Mladenovic et al, 1995; Rozman, 2002). Moreover, large inter-individual variability has been observed in the steady-state plasma concentrations of A77 1726 among patients taking therapeutic doses of leflunomide, with an 80-fold concentration range observed between the highest and lowest values (Bohanec Grabar et al, 2009; Chan et al, 2005; Keen et al, 2013; van Roon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…At the standard daily dosage of 20 mg leflunomide, the average steady-state plasma concentration of A77 1726 is approximately 125 μM (Bohanec Grabar et al, 2009; Rozman, 2002). Pharmacokinetic studies have shown that plasma/serum concentrations of A77 1726 are dose proportional following either single (20–100 mg) or repeated doses (5–25 mg daily) of leflunomide (Li et al, 2002; Mladenovic et al, 1995; Rozman, 2002). Moreover, large inter-individual variability has been observed in the steady-state plasma concentrations of A77 1726 among patients taking therapeutic doses of leflunomide, with an 80-fold concentration range observed between the highest and lowest values (Bohanec Grabar et al, 2009; Chan et al, 2005; Keen et al, 2013; van Roon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The present work employed the lowest plasma sample volume and had higher sensitivity (LLOQ at 10 ng/mL) compared with most previous reports, with LLOQ ranging from 50 ng/mL to 10 μg/mL (Schmidt et al, ; Chan et al, ; Sobhani et al, ; Rule et al, ). Across a 500‐fold calibration curve the range was adequate to cover the TER plasma concentration range referring to the existing studies (Li et al, ). However, a 1000‐fold calibration curve range was too large for urine concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Blank human urine and plasma were used to prepare calibration standards and QC samples by diluting corresponding stock solutions. The lower limit of quantification (LLOQ) for TER was selected according to concentrations reported in previous studies (Roussel, ; Li et al, ; Lim et al, ), and ensured a signal‐to‐noise ratio >5. The final plasma concentration of calibration standards for TER and 4‐TMOA were 10, 20, 50, 100, 500, 1000, 2500 and 5000 ng/mL, and concentrations at 25, 400 and 4000 ng/mL were set for QC samples.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown by pharmacodynamic studies that after oral administration, LEF is promptly converted to its active metabolic product, A771726, which has high albumin binding, and is reabsorbed via enterohepatic cycling. The half‐life of LEF is 5–40 days (15 days on average), but previous results have shown that the half‐life of LEF in Chinese patients is only about 8 days . This data suggests that the interval between the administrations of LEF doses could be safely extended.…”
Section: Introductionmentioning
confidence: 86%
“…The half-life of LEF is 5-40 days (15 days on average), 6 but previous results have shown that the half-life of LEF in Chinese patients is only about 8 days. 7 This data suggests that the interval between the administrations of LEF doses could be safely extended. Indeed, it has been reported that weekly administration of 100 mg LEF for RA has the same efficacy as that of the daily administration of 20 mg LEF.…”
Section: Introductionmentioning
confidence: 90%